1999
DOI: 10.1530/eje.0.1410481
|View full text |Cite
|
Sign up to set email alerts
|

Observational study in adult hypopituitary patients with untreated growth hormone deficiency (ODA study). Socio-economic impact and health status. Collaborative ODA (Observational GH Deficiency in Adults) Group

Abstract: Objective: The aim of the present study was to assess the socio-economic impact at baseline and after one year of follow-up of clinical and health status characteristics and laboratory tests of adult-onset GH deficiency (AGHD), a well-known clinical entity, in a large group of Spanish hypopituitary patients with untreated AGHD. Design and Methods: A total of 926 eligible patients with GHD (GH Յ 5 ng/ml after stimulation) and at least one further pituitary hormone deficiency were retrospectively studied; 356 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
1
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 33 publications
6
23
1
3
Order By: Relevance
“…Sanmarti et al reported that the prevalence of hypertension was higher in GH-deficient patients (22%) than in the general population in Spain [22]. In our series, hypertension was observed only in one male patient.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Sanmarti et al reported that the prevalence of hypertension was higher in GH-deficient patients (22%) than in the general population in Spain [22]. In our series, hypertension was observed only in one male patient.…”
Section: Discussioncontrasting
confidence: 55%
“…In this study, 90% (36/40) of the patients with gonadotropin deficiency were receiving sex hormone replacement therapy, although it was not clear whether the replacement of sex hormones affected the severity and number of metabolic comorbidities in our patients. Concerning the number of overlapped metabolic co-morbidities in one person in the Japanese general population, an analysis using Japanese criteria for metabolic syndrome, in a report by the Ministry of Health, Labour and Welfare, found the prevalence of Japanese men who had one, two, and three metabolic risk factors (dyslipidemia, elevated blood pressure, or glucose intolerance) increased with age from 31% (20-29 year age group) to 53% (50-59 year age group), from 4% (20-29) to 23% (50-59), and from 0.8% (20)(21)(22)(23)(24)(25)(26)(27)(28)(29) to 7% (50-59), respectively. The prevalence of Japanese women who had one, two, and three of these component factors increased from 5% (20-29 year age group) to 46% (50-59 year age group), from 0% (20-29) to 18% (50-59), and from 0% (20)(21)(22)(23)(24)(25)(26)(27)(28)(29) to 4% (50-59), respectively [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sanmarti et al (24) conducted a retrospective study of the health status of 926 hypopituitary patients with adult-onset GHD who were not treated with GH, including 1-year follow-up data, which were available in 356 patients. Clinical evaluations and laboratory tests showed a higher incidence of cardiovascular risk factors.…”
Section: Lipids Of Gh-deficient Patients In Clinical Studiesmentioning
confidence: 99%
“…Cardiovascular risk factors described in this population include altered body composition with truncal adiposity, detrimental changes in lipid profile, insulin resistance and impaired exercise capacity, among others (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%